On the role of water resources management to transform water, energy, food and ecosystem (WEFE) systems in transboundary river basins [Abstract only] - Uhlenbrook, Stefan; Ringler, Claudia; Lautze, Jonathan F.; McCartney, Matthew P.; Hafeez, Mohsin (Copernicus GmbH, 2022)
The program NEXUS Gains addresses key challenges of transforming water, energy, food and ecosystem (WEFE) systems in transboundary bread-basket basins in East and Southern Africa (Blue Nile and Limpopo basins), Central (Aral Sea basin) and South Asia (Ganges and Indus basin) in a changing world. The program particularly explores water resource management options to understand WEFE system interdependencies, trade-offs and synergies and develop more sustainable development pathways for all members society.